A kind of microcrystalline glass with low dielectric loss and its preparation method and application

By adopting a cyclic heat treatment process of heating first, then cooling and then heating during the preparation process of microcrystalline glass, the problem of excessive dielectric loss of existing microcrystalline glass is solved, and the dielectric loss requirements of 5G systems are significantly reduced, which is achieved.

CN119774885APending Publication Date: 2025-04-08SICHUAN HONGKE INNOVATION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411985799.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The dielectric loss of existing microcrystalline glasses is too high in 5G environment, resulting in poor signal transmission effect and it is difficult to meet the requirements of 5G systems for dielectric loss value.

Method used

The cyclic heat treatment process is adopted that first heat-raising, then cools down and then heat-raising, optimizes the structure and chemical composition of microcrystalline glass, reduces its dielectric loss and improves insulation performance.

Benefits of technology

Through the cyclic heat treatment process, the dielectric loss of crystallized glass is significantly reduced, so that the ratio of its dielectric loss tangent tanδ*1000 to the relative dielectric constant ε is below 1.0, meeting the dielectric loss requirements of 5G systems, and at the same time improving the mechanical strength and drop resistance of the glass.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005222545690000091
    Figure BDA0005222545690000091
  • Figure BDA0005222545690000101
    Figure BDA0005222545690000101
  • Figure BDA0005222545690000131
    Figure BDA0005222545690000131
Patent Text Reader

Abstract

The present application relates to the field of glass manufacturing, and specifically discloses a low dielectric loss microcrystalline glass, its preparation method and application. In the preparation method of this microcrystalline glass, by optimizing the raw material composition ratio, and adopting a heat treatment crystallization process of first heating, then cooling, and then heating again, the structure and chemical composition of the microcrystalline glass are optimized, thereby reducing its dielectric loss and improving its insulation performance. The crystals of the obtained microcrystalline glass are mainly lithium disilicate crystals. At 1MHz and 24℃, the ratio of the dielectric loss tangent tanδ*1000 to the relative dielectric constant ε is below 1.0, which can meet the applicability in the 5G environment and can be used for mobile phone covers, tablet computer covers, watch covers, and car display covers, etc., with broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of glass manufacturing, and more specifically, to a low dielectric loss microcrystalline glass and a preparation method and application thereof. Background Art

[0002] With the rapid development of 5G communication technology, the demand for smart mobile terminals is growing. These devices not only need to have high-performance computing capabilities and convenient operating experience, but also need to have excellent physical properties, such as high strength and good electromagnetic wave transmittance. Especially in the selection of protective back cover materials, traditional metal materials are no longer suitable for the requirements of the 5G era due to their high attenuation coefficient for electromagnetic wave signals. Therefore, glass materials have become the preferred material for the protective back cover of 5G smart mobile terminals due to their high transparency and strong signal transmittance.

[0003] At present, in order to meet the above needs, the commonly used solution in the industry is to use ordinary microcrystalline glass. This kind of glass usually optimizes its performance by adjusting its component ratio. Common components include silicon dioxide, aluminum oxide, sodium oxide, etc. In addition, some improvement measures also include adding a small amount of rare earth element oxides to further improve the comprehensive performance of the glass. The specific preparation process generally includes steps such as raw material ratio, mixed melting, casting and heat treatment, aiming to form the glass into the required microstructure and mechanical properties. However, the existing solutions still face many challenges in practical applications. First, the simple adjustment of the component ratio is difficult to completely solve the problem of excessive dielectric loss, resulting in poor signal transmission effect. Secondly, although the addition of rare earth elements can improve certain properties, how to accurately control their content and distribution remains a difficult problem. Finally, improper selection of temperature and time parameters during heat treatment may lead to uneven crystal particle size, which in turn affects the performance stability of the final product.

[0004] Although the existing microcrystalline glass can meet some application requirements to a certain extent, there is still a significant bottleneck in reducing dielectric loss. The 5G system requires that the ideal dielectric loss value should be less than 0.01, while the dielectric loss value of microcrystalline glass in the existing technology is usually around 0.03, and there is a significant gap between the two. Especially in the process of high-frequency signal transmission, excessive dielectric loss will cause serious signal attenuation, thereby affecting the communication quality and efficiency of the equipment. Therefore, how to effectively reduce the dielectric loss of microcrystalline glass and improve its applicability in the 5G environment has become a technical problem that needs to be solved urgently. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a low dielectric loss glass-ceramic and its preparation method and application. The present application can optimize the structure and chemical composition of the glass-ceramic through a cyclic heat treatment process of first heating, then cooling, and then heating again, thereby reducing its dielectric loss and improving its insulation performance.

[0006] This application adopts the following technical solutions:

[0007] In a first aspect, the present application provides a method for preparing a microcrystalline glass with low dielectric loss, wherein the crystals of the microcrystalline glass are mainly lithium disilicate crystals, and at 1 MHz and 24° C., the ratio of the dielectric loss tangent tanδ*1000 to the relative dielectric constant ε is less than 1.0;

[0008] The preparation method thereof comprises:

[0009] The raw materials are mixed uniformly according to the composition ratio of the oxides, placed in a melting furnace, melted at a temperature range of 1380 to 1520°C for 1.5 to 3 hours, and then clarified, homogenized, formed, and annealed to obtain bulk glass;

[0010] Then, the main glass is subjected to a cyclic heat treatment in the range of 550-770° C. by first heating up, then cooling down, and then heating up again, and then kept at 750-770° C. for 1-2 hours to obtain a glass-ceramic original sheet;

[0011] The original glass-ceramic sheet is placed in a mixed strengthening liquid for chemical strengthening to obtain the glass-ceramic sheet.

[0012] Furthermore, the above-mentioned cyclic heat treatment process includes:

[0013] The main glass is placed in a crystallization furnace, the temperature is raised to 550-570°C at a rate of 5-7°C / min, the temperature is raised to 660-680°C at a rate of 1-3°C / min, the temperature is lowered to 590-610°C at a rate of 1-3°C / min, and finally the temperature is raised to 750-770°C at a rate of 0.5-1.5°C / min. This is one cycle;

[0014] The temperature is then lowered to 550-570°C at a rate of 2-4°C / min to start the next cycle, and the resulting glass is then heated to 750-770°C and kept warm for 1-2 hours to obtain a raw glass-ceramic sheet.

[0015] Furthermore, in terms of mass percentage of oxides, the composition of glass-ceramics is:

[0016] SiO2: 69-73.8%;

[0017] Al2O3: 6-8.8%;

[0018] Na2O: 0.2-1.5%;

[0019] K2O: 0.1~0.9%;

[0020] Li2O: 11.5~13.8%;

[0021] ZrO2: 5.5~6.8%;

[0022] P2O5: 1.6~2.8%.

[0023] Furthermore, in the above process of preparing the bulk glass, the clarification temperature is 1560-1610° C. and the insulation time is 1-3 hours.

[0024] Furthermore, in the above process of preparing the bulk glass, the molding includes cooling the temperature of the clarified glass liquid to 1250-1300° C. within 35-45 minutes, and then transferring the glass liquid into a mold for molding.

[0025] Furthermore, in the above process of preparing the bulk glass, the annealing temperature is 480-580° C. and the holding time is 1-3 hours.

[0026] Furthermore, in the above-mentioned process of chemically strengthening the microcrystalline glass original sheet, the mixed strengthening liquid is obtained by mixing NaNO3 and KNO3 molten salt, wherein the mass fraction of KNO3 is 83-88wt%.

[0027] Furthermore, in the process of chemically strengthening the glass-ceramic original sheet, the strengthening temperature is 455-465° C., and the strengthening time is 270-290 min.

[0028] In the second aspect, the present application provides a low dielectric loss microcrystalline glass, which is obtained by the above-mentioned preparation method, and the crystals of the microcrystalline glass are mainly lithium disilicate crystals. At 1 MHz and 24°C, the ratio of the dielectric loss tangent tanδ*1000 to the relative dielectric constant ε is below 1.0, the average grain size of the microcrystalline glass is 16 to 30 nm, and the haze is less than 0.20% at a thickness of 0.70 mm.

[0029] In a third aspect, the present application provides an application of the above-mentioned low dielectric loss microcrystalline glass in mobile phone cover plates, tablet computer cover plates, watch cover plates and automobile display cover plates.

[0030] In summary, this application has the following beneficial effects:

[0031] 1. Due to the preparation method provided by the present application, in the glass crystallization process, a cyclic heat treatment method is adopted, that is, a cyclic heat treatment process of first heating, then cooling, and then heating is carried out in the range of 550-770°C. For example, the temperature changes in sequence as follows: 560°C-670°C-600°C-760°C (this is one cycle), repeating the cycle 1-3 times, and then keeping warm at 750-770°C for 1-2h. This cyclic heat treatment in a specific way within a specific temperature range helps to optimize the ratio of the crystalline phase to the glass phase, making the microcrystalline glass structure more compact to reduce dielectric loss. And because the dielectric loss is related to the concentration and migration ability of alkali metal ions, in the heating stage, the activity of alkali metal ions in the glass phase increases, which helps their migration and redistribution; and in the cooling stage, as the temperature decreases, the activity of alkali metal ions decreases, reducing their migration loss under the action of the electric field. At the same time, the cyclic heat treatment process can promote the precipitation and growth of crystals to form more uniform and fine grains, which helps to reduce defects and stress concentration at grain boundaries, thereby reducing dielectric losses.

[0032] 2. The inventors have also shown through experiments that when the dielectric loss of microcrystalline glass is tested at different frequencies and temperatures, it is found that the dielectric loss of microcrystalline glass treated by the cyclic process is relatively low at high frequencies and high temperatures. This is because the cyclic process helps to reduce the relaxation deformation of the glass network and the energy absorbed by the intrinsic vibration of ions or skeletons outside the network, thereby reducing the dielectric loss.

[0033] 3. In a preferred embodiment of the present application, the content of alkali metal ions in the microcrystalline glass is reduced by optimizing the composition and ratio of oxides in the microcrystalline glass, and the chemical composition of the glass phase is optimized by coordinated cyclic heat treatment process to further reduce the dielectric loss of the glass. DETAILED DESCRIPTION

[0034] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0035] The technical solution of the present invention is:

[0036] The microcrystalline glass provided in this embodiment is mainly composed of lithium disilicate crystals. At 1 MHz and 24°C, the ratio of the dielectric loss tangent tanδ*1000 to the relative dielectric constant ε is below 1.0, which can meet the requirements of the 5G system for an ideal dielectric loss value, and at the same time has the characteristics of high mechanical strength and excellent drop resistance.

[0037] The inventive concept of the present application is as follows: the dielectric constant refers to the ratio of the electric energy of the two electric fields established in the dielectric material and in the vacuum. If an electric field is established in the dielectric, the electric energy is stored in the material, and when the electric field is removed, the electric energy is completely restored. However, usually only part of the energy can be restored, and the lost part of the electric energy is manifested as heat. Therefore, in an AC electric field, the insulating material has electric energy loss. The ratio of the irrecoverable part of the electric energy to the recoverable part is expressed by the dielectric loss tangent (tanδ). The dielectric loss is related to the dielectric constant or dielectric constant ε of the material, and the dielectric loss factor is the product of the dielectric constant and the dielectric loss tangent, that is, ε·tanδ.

[0038] Dielectric loss includes conductivity loss, ion migration loss, deformation and vibration loss, etc. When the frequency is lower than 1MHz, conductivity and ion migration loss become very important; when the frequency is about 10MHz, the other two forms of loss are dominant. Conductivity loss and ion migration loss are mainly determined by the concentration and migration ability of alkali metal ions. Therefore, at low frequencies, alkali metal ions have high activity in the residual glass phase, while in the crystal phase, such ions have little effect on dielectric loss.

[0039] Furthermore, when alkali metal ions are incorporated into the crystalline phase, the power factor decreases significantly as the glass crystallizes. In lithium aluminum silicate glass-ceramics, the main crystalline phase is lithium disilicate, and lithium ions are incorporated into this crystal, which reduces its mobility and thus reduces the dielectric loss of the material. If the mobile alkali metal ions (such as Na+) do not participate in the crystalline phase composition, but are enriched in the residual glass phase, the glass-ceramics will have high dielectric loss.

[0040] Therefore, in order to improve the radio wave transmittance, the inventors optimized the oxide composition ratio and the heat treatment process of the crystallization process to make the relative dielectric constant and dielectric loss tangent smaller. In addition, the radio wave transmittance of the crystallized glass may be affected by the radio wave transmittance of the crystals it contains, and the relative dielectric constant of lithium disilicate crystals is particularly small. Therefore, it is necessary to make the crystals of the microcrystalline glass mainly lithium disilicate crystals to improve the radio wave transmittance.

[0041] The method for preparing the microcrystalline glass comprises the following steps:

[0042] Step S1, mixing:

[0043] The raw materials are mixed uniformly according to the component ratio of the oxides.

[0044] Furthermore, calculated by mass percentage of oxides, the components of the microcrystalline glass are: SiO2: 69-73.8%; Al2O3: 6-8.8%; Na2O: 0.2-1.5%; K2O: 0.1-0.9%; Li2O: 11.5-13.8%; ZrO2: 5.5-6.8%; P2O5: 1.6-2.8%.

[0045] SiO2 is a component that constitutes lithium disilicate crystals and is an essential component. SiO2 is a component that constitutes the glass network and is also a component that improves chemical durability. The content of SiO2 is preferably 55-85%; in order to improve chemical durability and chemical strengthening properties, the content of Al2O3 is preferably 6.5-8.5%.

[0046] Na2O is a component that forms a surface compressive stress layer in a chemical strengthening treatment using potassium salts, and is also a component that can improve the solubility of glass. In addition, Na is an element that can exist as a heterogeneous element in the Li ion site of lithium disilicate crystals. The content of Na2O is preferably 0.2 to 1.5%, preferably 0.4 to 1.2%.

[0047] K2O is a component that improves the solubility of glass and also a component that improves ion exchange performance. The content of K2O is preferably 0.2 to 0.7%.

[0048] Li2O is a component that forms surface compressive stress through ion exchange and is also a component that improves the solubility of glass. By making the crystallized glass contain Li2O, a stress distribution with large surface compressive stress and compressive stress layer is obtained by ion-exchanging Li ions on the surface of the glass with Na ions and then exchanging Na ions with K ions. The content of Li2O is preferably 12.2-13.5%.

[0049] ZrO2 is a component that can increase the surface compressive stress of chemically strengthened glass, and the content of ZrO2 is preferably 5.8-6.3%. P2O5 is a component that becomes the crystal nucleus of lithium disilicate crystals. From the perspective of precipitating lithium disilicate crystals, the content of P2O5 is preferably 1.9-2.4%.

[0050] Step S2, preparing the bulk glass:

[0051] The uniformly mixed raw materials are placed in a melting furnace, melted at a temperature range of 1380 to 1520°C for 1.5 to 3 hours, and then clarified, homogenized, formed, and annealed to obtain bulk glass;

[0052] Furthermore, the melting temperature is 1400-1500° C., and the holding time is 1.5-3 h; preferably, the melting temperature is 1420-1480° C., and the holding time is 2-2.5 h.

[0053] Furthermore, the clarification temperature is 1560-1610° C., and the holding time is 1-3 hours; preferably, the clarification temperature is 1565-1580° C., and the holding time is 1.5-2.5 hours.

[0054] Furthermore, the molding includes cooling the temperature of the clarified molten glass to 1250-1300° C. (preferably 1270-1290° C.) within 35-45 minutes (preferably 38-42 minutes), and then transferring the molten glass into a mold for molding.

[0055] Furthermore, the annealing temperature is 480-580° C., and the holding time is 1-3 hours; preferably, the annealing temperature is 500-560° C., and the holding time is 1.5-2.5 hours.

[0056] Step S3, preparing a glass-ceramic original sheet:

[0057] The main glass is then subjected to a cyclic heat treatment at 550-770°C, wherein the temperature is first increased, then decreased, and then increased again, and then kept at 750-770°C for 1-2 hours to obtain a glass-ceramic original sheet;

[0058] Furthermore, the above-mentioned cyclic heat treatment process includes:

[0059] (1) placing the main glass in a crystallization furnace, raising the temperature to 550-570°C at a rate of 5-7°C / min, raising the temperature to 660-680°C at a rate of 1-3°C / min, lowering the temperature to 590-610°C at a rate of 1-3°C / min, and finally raising the temperature to 750-770°C at a rate of 0.5-1.5°C / min. This is one cycle;

[0060] (2) Then, the temperature is lowered to 550-570° C. at a rate of 2-4° C. / min, and the next cycle is started. Then, the obtained glass is kept at 750-770° C. for 1-2 hours to obtain a raw glass-ceramic sheet.

[0061] Preferably, the above-mentioned cyclic heat treatment process includes: placing the main glass in a crystallization furnace, raising the temperature to 560°C at a rate of 6°C / min, raising the temperature to 670°C at a rate of 2°C / min, then reducing the temperature to 600°C at a rate of 2°C / min, and then raising the temperature to 760°C at a rate of 1°C / min, from 560°C-670°C-600°C-760°C as a cycle, reducing the temperature to 560°C at a rate of 3°C / min, starting the next cycle, and after 1-3 cycles, keeping warm at 760°C for 1.5 hours, then turning off the power to the equipment, and cooling to room temperature with the furnace to obtain microcrystalline glass.

[0062] Step S4, chemical strengthening:

[0063] The original microcrystalline glass sheet is placed in a mixed strengthening liquid for chemical strengthening to obtain microcrystalline glass.

[0064] Furthermore, the chemical strengthening is a single strengthening. The mixed strengthening liquid is obtained by mixing NaNO3 and KNO3 molten salt, wherein the mass fraction of KNO3 is 83-88wt%, preferably 84-86wt%. The strengthening temperature is 455-465°C, and the strengthening time is 270-290min; preferably, the strengthening temperature is 458-463°C, and the strengthening time is 275-285min.

[0065] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0066] Example

[0067] Examples 1-6

[0068] This group of embodiments provides a low dielectric loss glass-ceramic, and the preparation method thereof includes:

[0069] (1) Prepare raw materials according to the mass fractions of oxides shown in Table 1;

[0070] Table 1.

[0071]

[0072]

[0073] (2) After the raw materials are mixed evenly, they are placed in a corundum crucible, and then the corundum crucible is placed in a melting furnace, melted within a temperature range of 1510°C for 2 hours, and then heated to a clarifying temperature of 1570°C, and kept warm for 2 hours. Subsequently, the above molten liquid is cooled to 1280°C within 40 minutes, and then transferred into a mold for forming, and finally the formed glass is transferred into an annealing furnace, at which time the temperature in the annealing furnace is 540°C, kept warm for 2 hours, and then the power is turned off, and the furnace is naturally cooled to obtain the bulk glass.

[0074] (3) The annealed glass is subjected to a cyclic heat treatment, specifically, the temperature is raised to 560°C at a rate of 6°C / min, then raised to 670°C at a rate of 2°C / min, then lowered to 600°C at a rate of 2°C / min, and then raised to 760°C at a rate of 1°C / min. The temperature from 560°C-670°C-600°C-760°C is one cycle. Then the temperature is lowered to 560°C at a rate of 3°C / min, and the next cycle is started. After one cycle, the equipment is kept at 760°C for 1.5 hours, and then the equipment is powered off. The equipment is cooled to room temperature along with the furnace to obtain microcrystalline glass.

[0075] (4) The microcrystalline glass is mechanically processed to obtain a microcrystalline glass original sheet with a size of 147*63*0.7 mm; the obtained microcrystalline glass original sheet is placed in a mixed strengthening liquid of NaNO3:KNO3=15%:85% for strengthening treatment, and strengthened at a temperature of 460°C for 280 minutes to obtain a strengthened microcrystalline glass.

[0076] Example 7

[0077] The difference between this embodiment and embodiment 1 is step (3):

[0078] The annealed glass is subjected to cyclic heat treatment, specifically, the temperature is increased to 550°C at a rate of 6°C / min, then increased to 660°C at a rate of 2°C / min, then decreased to 590°C at a rate of 2°C / min, then increased to 750°C at a rate of 1°C / min, and one cycle is from 550°C-660°C-590°C-750°C, then decreased to 550°C at a rate of 3°C / min, and the next cycle is started. After one cycle, the equipment is kept at 750°C for 1.5 hours, then the equipment is powered off and cooled to room temperature with the furnace to obtain microcrystalline glass.

[0079] Example 8

[0080] The difference between this embodiment and embodiment 1 is step (3):

[0081] The annealed glass is subjected to cyclic heat treatment, specifically, the temperature is increased to 570°C at a rate of 6°C / min, the temperature is increased to 680°C at a rate of 2°C / min, the temperature is then decreased to 610°C at a rate of 2°C / min, and then the temperature is increased to 770°C at a rate of 1°C / min. One cycle is from 570°C to 680°C to 610°C to 770°C, and the temperature is then decreased to 570°C at a rate of 3°C / min to start the next cycle. After one cycle, the equipment is kept at 770°C for 1.5 hours, the equipment is powered off, and the glass is cooled to room temperature along with the furnace to obtain microcrystalline glass.

[0082] Example 9

[0083] The difference between this embodiment and embodiment 1 is step (2):

[0084] After the raw materials are mixed evenly, they are placed in a corundum crucible, and then the corundum crucible is placed in a melting furnace, melted within a temperature range of 1520°C for 1.5 hours, and then heated to a clarifying temperature of 1610°C, and kept warm for 3 hours. Subsequently, the above molten liquid is cooled to 1300°C within 45 minutes, and then transferred into a mold for forming, and finally the formed glass is transferred into an annealing furnace, at which time the temperature in the annealing furnace is 580°C, kept warm for 1 hour, and then the power is turned off, and naturally cooled with the furnace to obtain the bulk glass.

[0085] Example 10

[0086] The difference between this embodiment and embodiment 1 is step (2):

[0087] After the raw materials are mixed evenly, they are placed in a corundum crucible, and then the corundum crucible is placed in a melting furnace, melted within a temperature range of 1380°C for 3 hours, and then heated to a clarifying temperature of 1560°C and kept warm for 2.5 hours. Subsequently, the above molten liquid is cooled to 1250°C within 35 minutes, and then transferred into a mold for forming, and finally the formed glass is transferred into an annealing furnace, at which time the temperature in the annealing furnace is 480°C, kept warm for 2.5 hours, and then the power is turned off, and the furnace is naturally cooled to obtain the bulk glass.

[0088] Embodiment 11

[0089] The difference between this embodiment and embodiment 1 is step (4):

[0090] The microcrystalline glass is mechanically processed to obtain a microcrystalline glass original sheet with a size of 147*63*0.7mm; the obtained microcrystalline glass original sheet is placed in a mixed strengthening liquid of NaNO3:KNO3=12%:88% for strengthening treatment, and strengthened at a temperature of 463°C for 275 minutes to obtain a strengthened microcrystalline glass.

[0091] Example 12

[0092] The difference between this embodiment and embodiment 1 is step (4):

[0093] The microcrystalline glass is mechanically processed to obtain a microcrystalline glass original sheet with a size of 147*63*0.7mm; the obtained microcrystalline glass original sheet is placed in a mixed strengthening liquid of NaNO3:KNO3=17%:83% for strengthening treatment, and strengthened at a temperature of 455°C for 290 minutes to obtain a strengthened microcrystalline glass.

[0094] Comparative Example

[0095] Comparative Examples 1-3

[0096] The difference between this comparative example and Example 1 is that the components of the raw materials are as shown in Table 2:

[0097] Table 1.

[0098]

[0099] Comparative Example 4

[0100] The difference between this comparative example and Example 1 lies in the crystallization process of step (3):

[0101] The annealed glass is placed at 560°C for nucleation for 2 hours, and then placed at 900°C for crystallization for 1 hour. The equipment is then powered off and cooled to room temperature to obtain microcrystalline glass.

[0102] Comparative Example 5

[0103] The difference between this comparative example and Example 1 lies in the crystallization process of step (3):

[0104] The annealed glass is subjected to cyclic heat treatment. Specifically, the temperature is increased to 560°C at a rate of 6°C / min, then increased to 670°C at a rate of 2°C / min, then decreased to 600°C at a rate of 2°C / min, and then increased to 760°C at a rate of 1°C / min. After keeping the temperature for 1.5 hours, the equipment is powered off and cooled to room temperature in the furnace to obtain microcrystalline glass.

[0105] Comparative Example 6

[0106] The difference between this comparative example and Example 1 lies in the crystallization process of step (3):

[0107] The annealed glass is subjected to cyclic heat treatment. Specifically, the temperature is increased to 560°C at a rate of 6°C / min, and then increased to 760°C at a rate of 2°C / min. One cycle is from 560°C to 760°C, and then the temperature is reduced to 560°C at a rate of 2°C / min. After repeating one cycle, the temperature is kept at 760°C for 1.5 hours, the equipment is powered off, and the glass is cooled to room temperature along with the furnace to obtain microcrystalline glass.

[0108] Performance testing

[0109] Detection method / test method

[0110] 1) Haze measurement:

[0111] A haze tester, Minolta CM3600A, was used to prepare samples with a thickness of less than 1 mm and the test was carried out according to the standard of GB2410-80.

[0112] 2) Grain size determination:

[0113] Using a SEM scanning electron microscope, the microcrystalline glass is surface treated in HF acid, gold is sprayed on the surface of the microcrystalline glass, and the surface is scanned under the SEM scanning electron microscope to determine the size of its grains.

[0114] 3) Radio wave transmittance measurement

[0115] The relative dielectric constant ε and dielectric loss tangent tan δ were measured at 1 MHz and 24° C. using a network analyzer by a separated pin dielectric resonator method (SPDR method).

[0116] 4) Determination of stress layer depth:

[0117] The depth of the glass stress layer was tested using an Orihara SLP-2000 stress meter.

[0118] 5) Sandpaper drop test:

[0119] The sandpaper drop test was conducted using a drop test machine model XH-YF1000. The test conditions were: 180-grit sandpaper, the total weight of the test glass sample and the fixture was 186 grams, the base height was 50 cm, and the test was performed 5 cm at a time, once at each height, until the glass broke.

[0120] The measurement results are shown in Table 3 and Table 4:

[0121] Table 3.

[0122]

[0123]

[0124] As can be seen from Table 3, compared with Comparative Examples 1-3, the relative dielectric constant and dielectric loss tangent of the microcrystalline glass provided in Examples 1-6 of the present application are respectively smaller, and at 1MHz and 24°C, the ratio of dielectric loss tangent tanδ*1000 to relative dielectric constant ε is less than 1.0, and at the same time, the haze, transmittance and sandpaper drop height are all improved. This shows that Examples 1-6 of the present application reduce dielectric loss by optimizing the raw material component ratio, increasing the content of lithium disilicate in the main crystalline phase, and reducing the mobility of alkali metal ions.

[0125] Table 4.

[0126]

[0127]

[0128] It can be seen from Table 4 that:

[0129] Comparative Example 4 adopts the existing crystallization process. Although the other properties of the finally obtained microcrystalline glass are close to those of Example 1, the dielectric constant and dielectric loss tangent are larger. At 1 MHz and 24°C, the ratio of dielectric loss tangent tanδ*1000 to relative dielectric constant ε is 1.88. Its dielectric loss is large, and it is difficult to apply to 5G system requirements.

[0130] Although Comparative Example 5 adopts a crystallization heat treatment process similar to that of Example 1 of the present application, cyclic heat treatment is not performed; while Comparative Example 6 adopts a heat treatment process of 560-760°C and repeats one cycle. From the results, the ratio of the dielectric loss tangent tanδ*1000 to the relative dielectric constant ε of the obtained microcrystalline glass at 1MHz and 24°C is greater than 1.5. This shows that the microcrystalline glass obtained by the cyclic heat treatment process of first heating up, then cooling down, and then heating up at a specific temperature adopted in Example 1 of the present application has relatively low dielectric loss at high frequency and high temperature. This is because this cyclic heat process helps to optimize the ratio of the crystal phase to the glass phase, making the microcrystalline glass structure denser; at the same time, it can also reduce the relaxation deformation of the glass network and the energy absorbed by the intrinsic vibration of the ions or skeleton outside the network, thereby reducing the dielectric loss.

[0131] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A method for preparing microcrystalline glass with low dielectric loss, characterized in that: The crystals of the microcrystalline glass are mainly lithium disilicate crystals, and at 1 MHz and 24° C., the ratio of the dielectric loss tangent tanδ*1000 to the relative dielectric constant ε is less than 1.0; The preparation method thereof comprises: The raw materials are mixed uniformly according to the composition ratio of the oxides, placed in a melting furnace, melted at a temperature range of 1380 to 1520°C for 1.5 to 3 hours, and then clarified, homogenized, formed, and annealed to obtain bulk glass; The main body glass is subjected to a cyclic heat treatment at 550-770° C. by first heating, then cooling, and then heating again, and then kept at 750-770° C. for 1-2 hours to obtain a glass-ceramic original sheet; The original glass-ceramics sheet is placed in a mixed strengthening liquid for chemical strengthening to obtain glass-ceramics.

2. The method for preparing low dielectric loss glass-ceramics according to claim 1, characterized in that: The cyclic heat treatment process comprises: The main body glass is placed in a crystallization furnace, the temperature is raised to 550-570°C at a rate of 5-7°C / min, the temperature is raised to 660-680°C at a rate of 1-3°C / min, the temperature is lowered to 590-610°C at a rate of 1-3°C / min, and finally the temperature is raised to 750-770°C at a rate of 0.5-1.5°C / min, which is one cycle; The temperature is then lowered to 550-570°C at a rate of 2-4°C / min, and the next cycle is started. The resulting glass is then kept at 750-770°C for 1-2 hours to obtain the original microcrystalline glass sheet.

3. The method for preparing low dielectric loss glass-ceramics according to claim 1, characterized in that: Measured in terms of mass percentage of oxides, the composition of the glass-ceramics is: SiO2: 69-73.8%; Al2O3: 6-8.8%; Na2O: 0.2-1.5%; K2O: 0.1~0.9%; Li2O: 11.5~13.8%; ZrO2: 5.5~6.8%; P2O5: 1.6~2.8%.

4. The method for preparing low dielectric loss glass-ceramics according to claim 1, characterized in that: In the process of preparing the bulk glass, the clarification temperature is 1560-1610° C. and the heat preservation time is 1-3 hours.

5. The method for preparing low dielectric loss glass-ceramics according to claim 1, characterized in that: In the process of preparing the bulk glass, the molding includes cooling the temperature of clarified molten glass to 1250-1300° C. within 35-45 minutes, and then transferring the molten glass into a mold for molding.

6. The method for preparing low dielectric loss glass-ceramics according to claim 1, characterized in that: In the process of preparing the bulk glass, the annealing temperature is 480-580° C. and the heat preservation time is 1-3 hours.

7. The method for preparing low dielectric loss glass-ceramics according to claim 1, characterized in that: In the process of chemically strengthening the microcrystalline glass original sheet, the mixed strengthening liquid is obtained by mixing NaNO3 and KNO3 molten salt, wherein the mass fraction of KNO3 is 83-88wt%.

8. The method for preparing low dielectric loss glass-ceramics according to claim 1, characterized in that: During the chemical strengthening process of the microcrystalline glass original sheet, the strengthening temperature is 455-465° C. and the strengthening time is 270-290 min.

9. A low dielectric loss glass-ceramic, characterized in that: It is obtained by the preparation method as described in any one of claims 1 to 8, the crystals of the microcrystalline glass are mainly lithium disilicate crystals, at 1 MHz and 24°C, the ratio of the dielectric loss tangent tanδ*1000 to the relative dielectric constant ε is below 1.0, the average grain size of the microcrystalline glass is 16 to 30 nm, and at a thickness of 0.70 mm, the haze is <0.20%.

10. An application of the low dielectric loss glass-ceramic according to claim 9 in mobile phone cover plates, tablet computer cover plates, watch cover plates and automobile display cover plates.